Thymic T-Cell Production Is Associated With Changes in the Gut Microbiota in Young Chicks - Cheng, Jiaheng; Yuan, Yushan; Zhao, Fang; Chen, Jianwei; Chen, Peng; Li, Ying; Yan, Xia; Luo, Chenglong; Shu, Dingming; Qu, Hao; Ji, Jian (Frontiers in Immunology, 2021)
Increasing evidence shows that the gut microbiota holds a central role in immunity. However, its impact on the mediation of thymic T cells throughout life is not well understood. Chickens have been shown to be a valuable model for studying basic immunology. Here, we showed that gut microbiota mediates the development of thymic T cells in young chickens. Our results suggested that T cells sharply increased from day 0 and peaked at day 49. Interestingly, the α-diversity score pattern of change in gut microbiota increased after day 0 and continued to increase sequentially until day 49. More importantly, a decrease in the percentage and number of T cells in the thymus was found at early life (day 9 and day 49) after antibiotic treatment was evaluated by flow cytometry in broiler. Furthermore, antibiotic treatment resulted in a dramatic reduction in alpha diversity on day 9 and day 49, and Principal component analysis (PCA) also showed the microbiota were clearly separated into 2 clusters on day 9 and day 49 between the antibiotic and control groups. Furthermore, on day 9 and day 49, we identified 8 significantly different (P<0.05) microbes at the phylum level and 14 significantly different (P<0.05) genus between the antibiotic and control groups. Collectively, the intestinal microbiota was shown to be involved in the regulation of T cells in birds. Therefore, interventions that actively modify the gut microbiota in early life may accelerate the maturation of humoral immunity that confers anti-inflammatory effects against different pathogens.